5‐Amino‐6, 7, 8, 9‐Tetrahydrobenzo[b][1, 8]Naphthyridin‐2(1H)‐One: The first Example of a new Family of HuperTacrines for Alzheimer's Disease Therapy. Issue 8 (22nd March 2017) - Balmori, Alba; Chioua, Mourad; de la Bellacasa, Raimon Puig; Estrada‐Tejedor, Roger; Ismaili, Lhassane; Marco‐Contelles, José; Borrell, José I.
Abstract: In this communication we have described the synthesis of 2‐amino‐6‐oxo‐1, 6‐dihydropyridine‐3‐carbonitrile (4 ), and the preparation of 5‐amino‐6, 7, 8, 9‐tetrahydrobenzo[ b ][1, 8]naphthyridin‐2(1 H )‐one (3 a ), a non‐hepatotoxic, antioxidant agent, showing moderate, but selective human acetylcholinesterase inhibition. Abstract : The synthesis of 5‐amino‐6, 7, 8, 9‐tetrahydrobenzo [b] [1, 8]naphthyridin‐2(1 H )‐one (3 a ) from readily available intermediate 2‐amino‐6‐oxo‐1, 6‐dihydropyridine‐3‐carbonitrile (4 ) has been described. Compound3a is a non‐hepatotoxic, and antioxidant (2, 42 ± 0.06 TE) HuperTacrine, designed by juxtaposition of selected pharmacophoric motifs from acetylcholinesterase inhibitors huperzine A and tacrine, showing moderate, but selective hAChE inhibition (IC50 = 28.9 ± 1.5 μM). The interaction mechanism of product3 a has been investigated by induced fit docking.